Research Methods in the Dance Sciences - Mainwaring, Lynda; Ambegaonkar, Jatin P.; Welsh, Tom (Dance professor) (Book collections on Project MUSE., 2023)
"A comprehensive guide to conducting empirical research in dance Research Methods in the Dance Sciences introduces concepts and practices that support effective, empirical research in the dance sciences, including medical science. A valuable new resource for this growing field, this book provides foundational knowledge for anyone who wants to understand, apply, and conduct research with dancers and proposes ways to facilitate more collaboration between the many disciplines that often overlap in this area. In this volume, pioneers of dance medicine and science guide readers through the stages of the research process. They address topics such as choosing a research question, writing a literature review, developing a framework and methodology, influencing the field, and progressing in a research career. Offering dance-specific examples as illustrations, this volume provides clear and instructive strategies for developing a solid repertoire of research skills to examine dance and movement-centered activities. It is ideal for practicing and aspiring dancers, teachers, and clinicians in fields including exercise physiology, motor learning, behavioral sciences, food sciences, medicine, psychology, and somatics who are interested in dance science research. "--